City transport in a post carbon society - Banister, D (Edward Elgar, 2013)
The benefits of transport have been central to trade and globalization, and to new forms of networking between people and societies. But all of these activities have led to longer distances and more use of carbon-based fuels (Banister, 2011). While other sectors of the economy have decarbonized, transport has continued to increase its consumption of energy and its carbon dioxide (CO2) emissions. It now accounts for over 25 per cent of global CO2 and this figure is expected to increase to 50 per cent by 2030 (on 2005 levels), as other sectors decarbonize and as transport emissions continue to grow (NEAA, 2009; IEA, 2010). Global reduction targets have been set, suggesting that a 50 per cent reduction is needed by 2050 (on 1990 levels) in transport to avoid a 2oC increase in global temperatures and sea level rise (ITPS, 2011), and this means that the richer countries should be targeting an 80–90 per cent reduction over this period. Reaching such a reduction target is extremely difficult, but not impossible. At least in cities, there are clear means to create a transport system that uses very little carbon. For longer distance travel the options are far less apparent, and so available oil could be restricted to international aviation and shipping, and the carbon created could be offset through investment in clean energy projects.